2019
DOI: 10.1080/09658211.2019.1688835
|View full text |Cite
|
Sign up to set email alerts
|

Using metamemory measures and memory tests to estimate eyewitness free recall performance

Abstract: Using a mock witness methodology, we investigated the predictive value of metamemory measures and objective memory tests as indicators of eyewitness free recall performance. Participants (n = 208) first completed a metamemory assessment that included assessments of self-rated memory capacity, memory development and use of strategies. In a separate session, participants watched a mock crime video and provided a free recall account, followed by one out of four independent memory tests (i.e., free recall, cued re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
(107 reference statements)
3
12
0
Order By: Relevance
“…The model was fitted using the lme4 package v1.1–23 in R 4.0.2 (Bates et al, 2015) and p -values were obtained in the afex package v. 0.26–1 (Singmann et al, 2018). In line with existing research (e.g., Saraiva et al, 2020; Weber & Brewer, 2008; Wixted & Wells, 2017), the analyses revealed that confidence was a significant predictor of accuracy, χ 2 (1) = 1003.30, p < . 001.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The model was fitted using the lme4 package v1.1–23 in R 4.0.2 (Bates et al, 2015) and p -values were obtained in the afex package v. 0.26–1 (Singmann et al, 2018). In line with existing research (e.g., Saraiva et al, 2020; Weber & Brewer, 2008; Wixted & Wells, 2017), the analyses revealed that confidence was a significant predictor of accuracy, χ 2 (1) = 1003.30, p < . 001.…”
Section: Resultssupporting
confidence: 83%
“…To investigate this, participants watched one mock crime video, completed free recall and cued recall tests for details in the video, and then completed this procedure again for an alternative mock crime video. Research shows that eyewitness free recall reports are typically associated with high accuracy at every level of confidence, and responses are mostly given with high confidence (Saraiva et al, 2020). Therefore, we included cued-recall questions to produce enough variation in accuracy and confidence to plot stable calibration curves.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous research, we found that people’s beliefs about their general memory ability did not significantly predict their confidence when they recalled details shortly after witnessing a mock crime event (Saraiva et al, 2020). We predicted that self-rated memory ability would have a larger impact on confidence when the delay was long compared to when the delay was relatively short.…”
Section: Discussionsupporting
confidence: 87%
“…Second, as it is often not possible to check the objective accuracy of past events, ratings of memory confidence are often used as a way of evaluating the credibility of witnesses in legal settings. As demonstrated by the ART, there are individual differences in the recollective experience of autobiographical memory, and findings suggest that also ratings of memory confidence are somewhat stable across conditions, indicative of a trait-like characteristic (e.g., Saraiva et al, 2020). Future studies should examine how scores on the ART are related to ratings of memory confidence.…”
Section: Discussionmentioning
confidence: 92%